Effective Provisions of Educational Services for Native Arabic Learners with dyslexia at a Private School in Northern Emirates in the UAE A case-study - Alkamali, Hana (2020)
This study investigates the effectiveness of educational services provisions offered by an international bilingual private school in the Northern Emirates of the United Arab Emirates (UAE), for two Arabic students speaking English as an Additional Language (EAL) diagnosed with dyslexia. Using a qualitative, single case study approach, data were collected from observations, field notes, semi-structured interviews, and document analysis. The students were observed in inclusive general classrooms in Year 6, in English and Arabic, respectively, in addition to pull-out sessions for further English literacy support. Findings revealed that the school is providing both students with effective educational services, but the students are not able to access the Year 6 curriculum in English. There are no support services provided for Arabic literacy. A lack of coordination between teaching staff, administration and parents, and an unclear vision of inclusive education, had a negative impact. Recommendations include expanded inclusion and its development within the school environment; increased cooperation between all stakeholders with further support from the government; and within the school, an official policy of inclusion, flexible curricula, and teacher training in inclusion. Limitations of the study were partly due to access. Public schools were inaccessible due to government regulations; most private schools declined to allow access; and the school under study declined to provide official documents or policy statements. The observed students were limited in number (two), gender (both male), and grade level (both in Year 6). Future research could include more students from both genders and at different grade levels, in more schools in different areas of the UAE and the greater Gulf Cooperation Council (GCC). Of particular interest would be to investigate the effect of having bilingual 1:1 support assistant to maximize student literacy in both English and Arabic.